Improving English Vocabulary through Guess-the-Word Games Using Audio-Visual Media for Group B Children (Aged 5–6 Years) at TK Bhakti Siwi - Maulidiya, Siti; Zahro, Ianatuz; Siswono, Hendrik (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
This study aims to improve the English vocabulary mastery of Group B children (aged 5–6 years) at TK Bhakti Siwi through guess-the-word games based on audio-visual media. The research background stems from the children’s limited vocabulary, characterized by low interest, participation, and ability to mention and understand simple words. The study employed a Classroom Action Research (CAR) approach following the Kemmis and McTaggart model over two cycles, involving 10 children (4 boys and 6 girls). Data were collected through observation, documentation, and informal interviews, and analyzed qualitatively and descriptively by comparing the results of the pre-cycle, Cycle I, and Cycle II. The findings showed a significant improvement. In the pre-cycle, the average achievement was 0%, with nearly all children unable to name or understand vocabulary correctly. After Cycle I, the achievement increased to 20%, though not yet evenly distributed. In Cycle II, the achievement reached 80%, exceeding the minimum criterion in which at least 75% of children were categorized as A (Good). Almost all children were able to mention, understand, and use simple English words with more accurate pronunciation and confidence. The application of this medium also enhanced motivation, active participation, and enthusiasm, making it a suitable, interactive, and enjoyable strategy for English learning in early childhood education.